Islam Nusantara in the Traces of Kelopo Telu: Memories of the Kapu Merakurak Civilization of Tuban - Achmad Wildan An Nihrir; Dea Nur Syahira; Ilmi Wasiatul Khoiriyah; Nurul Hakim (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study aims to examine the role of Kelopo Telu as a representation of Islam Nusantara as well as a form of civilizational memory in Kapu Village, Merakurak District, Tuban Regency. Islam Nusantara is understood as a form of Islamic practice that is adaptive, moderate, and capable of accommodating local culture. This research employs a qualitative method with historical and anthropological approaches. Data were collected through in-depth interviews, participatory observation, and documentation, and then analyzed using data reduction, data display, and conclusion drawing, with triangulation techniques to ensure data validity. The results show that the da’wah of Kiai Kelopo Telu is reflected in three main aspects: physical traces, socio-cultural practices, and oral traditions. Religious activities at the Kelopo Telu Foundation, such as haul, tahlilan, religious gatherings, and other local traditions, represent the integration of Islamic teachings with local culture. These activities function not only as religious rituals but also as a medium for non-formal Islamic education, strengthening social cohesion, and transmitting values across generations. From the perspective of Islam Nusantara, the religious practices in Kelopo Telu reflect the values of moderation, tolerance, and respect for local traditions. Kelopo Telu also serves as a living collective memory continuously reproduced through social and religious practices. Therefore, Kelopo Telu is not merely a historical site, but also a symbol of a dynamic local Islamic civilization that remains relevant in contemporary society.